Tinjauan Etika Aksiologis Max Scheler dalam Tradisi Ngarot di Desa Karedok Kecamatan Jatigede Kabupaten Sumedang - Muwahidu Rifa (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The purpose of this paper is to answer the problems that are the subject of the research: 1) the Ngarot tradition in Karedok Village; 2) The procession of carrying out the Ngarot tradition in Karedok Village; and 3) Max Sheler's Akiological Ethics Analysis of the Ngarot tradition in Karedok Village. This research is a field research, using qualitative methods, and Max Scheler's value hierarchy theory as an analytical tool. The findings of this research are, first, historically, the Ngarot ceremony emerged as a community response to the situation that occurred at the end of 1900, Karedok village experienced a disaster that caused many people to get sick, even die, to crop failure. This tradition is a form of gratitude to Allah SWT for the abundance of gifts given. Second, the Ngarot ceremony is carried out in several stages, namely the slaughter of buffalo led by Kuncen and Lebe. Then the cultural carnival, mapag umbrella, tayuban art, and finally the village celebration. Third, the value of pleasure is reflected in the enthusiasm of the community, such as togetherness, cohesiveness, enjoying munding meat (buffalo) and in arts or folk entertainment. The value of life is reflected in the procession of slaughtering and burying buffalo heads and the art of tayuban. The spiritual value when Lebe reads the consent and continues with a prayer which is followed and agreed upon by the community. And the value of profanity is reflected in the concept of tradition itself and the use of munding jalu (male buffalo).